2017
DOI: 10.1111/jocn.13704
|View full text |Cite
|
Sign up to set email alerts
|

The role of the breast care nurse in patient and family care

Abstract: This study further delineates the important role that the nurses play in caring for patients and families during a critical time of their life. It extends further the frequency and importance of the supportive care and the need to educate their nurses on their role in providing spiritual care and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Evidence in the literature shows that the BCN is an integral member of the interprofessional team caring for patients undergoing breast surgery Halkett et al, 2006;Luck et al, 2017). The current study suggests that the timing of a patient's first consultation with a BCN and the mode of that consultation are determinants of the patient's overall outcomes, particularly in the areas of understanding diagnosis and treatment, feeling psychosocially supported, and receiving relevant practical support.…”
Section: Implications For Nursingmentioning
confidence: 70%
See 3 more Smart Citations
“…Evidence in the literature shows that the BCN is an integral member of the interprofessional team caring for patients undergoing breast surgery Halkett et al, 2006;Luck et al, 2017). The current study suggests that the timing of a patient's first consultation with a BCN and the mode of that consultation are determinants of the patient's overall outcomes, particularly in the areas of understanding diagnosis and treatment, feeling psychosocially supported, and receiving relevant practical support.…”
Section: Implications For Nursingmentioning
confidence: 70%
“…However, Halkett, Arbon, Scutter, and Borg (2006) have reported the importance that patients place on the BCN role while they are being treated; they described how patients found BCNs to provide important support throughout their treatment. Luck, Chok, Scott, and Wilkes (2017) described the importance of the BCN role from the perspective of BCNs, highlighting the part they play in sharing clinical expertise through providing patient education, coordinating care, and advocating for patients. However, the study failed to explore the patient perspective of receiving BCN support, which may differ from the perspective of BCNs delivering support.…”
Section: Timing and Mode Of Breast Carementioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of the study, the findings showed that breast care nurses should be included in the multidisciplinary breast cancer team. [16] In a study evaluating the roles of breast care nurses the as patient advocate, patient trainer, care coordinator and clinical expert roles, conducted by Luck et al [17] were determined in line with the theme. They reported that breast care nurses have important roles and functions in the maintenance process and the importance of supportive care frequency.…”
Section: Clinic Leadership: This Area Includes Competen-mentioning
confidence: 99%